Low-crystallinity rutile phase ruthenium manganese oxide catalyst and preparation method and application thereof

By preparing a low-crystalline rutile-phase rutile-phase rutile-phase rutile-based catalyst, the problems of poor stability and high production cost of Ru-based catalysts are solved, and the catalyst activity and stability are improved and the use of precious metals Ru is reduced. It is suitable for industrial electrocatalytic water oxidation.

CN119898831APending Publication Date: 2025-04-29DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411833923.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing Ru-based ruthenium oxide catalysts have poor stability during the redox electrocatalysis process, making it difficult to achieve industrial application, and the use of precious metal Ru is large, resulting in high production costs.

Method used

Using a low-crystalline rutile phase rutile-phase rutile-phase rutile-manganese oxide catalyst, the Mn3O4 powder is mixed with the Ru precursor solution, and centrifugation is performed to form a particle structure of nanoparticles aggregation, thereby improving the activity and stability of the catalyst.

Benefits of technology

It improves the activity and stability of the catalyst in the redox electrocatalysis process, reduces the use of precious metal Ru, reduces the production cost, and simplifies the preparation process, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898831A_ABST
    Figure CN119898831A_ABST
Patent Text Reader

Abstract

The invention discloses a low-crystallinity rutile phase ruthenium manganese oxide catalyst as well as a preparation method and application thereof, and belongs to the technical field of electro-catalysis. The low-crystallinity rutile phase ruthenium manganese oxide catalyst is of a nano-particle structure, the structure of the low-crystallinity rutile phase structure, and the preparation method of the low-crystallinity rutile phase ruthenium manganese oxide catalyst comprises the following steps: mixing prepared or commercially available manganous-manganic oxide powder with a ruthenium precursor solution, and fully reacting the manganous-manganic oxide powder and the ruthenium precursor solution through stirring or ultrasonic treatment; filtering, washing and drying to obtain precursor powder; and calcining the precursor powder, and cooling to room temperature to obtain the low-crystallinity rutile phase ruthenium manganese oxide catalyst. The method provided by the invention is simple to operate, mild in condition and low in production cost, and the low-crystallinity rutile phase ruthenium manganese oxide catalyst has outstanding activity and stability in the aspect of electro-catalysis water oxidation and has a good application prospect in the field of hydrogen production by proton exchange membrane water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a low-crystallinity rutile phase ruthenium manganese oxide catalyst and a preparation method and application thereof, belonging to the technical field of electrocatalysis. Background Art

[0002] By coupling renewable energy sources such as solar energy and wind energy with water electrolysis hydrogen production systems, green hydrogen can be produced on a large scale, realizing the conversion, storage and utilization of renewable energy. Among them, proton exchange membrane (PEM) water electrolysis technology has the advantages of being able to produce high-purity hydrogen at high current density and the system's rapid response can be well matched with intermittent renewable energy, and has attracted widespread attention at home and abroad. At present, in industrial PEM water electrolysis, the only anode electrocatalyst that can stably oxidize water is the scarce and expensive precious metal Ir, which greatly limits the large-scale application of PEM water electrolysis technology. The development of efficient and stable non-Ir-based oxygen evolution reaction (OER) electrocatalysts is crucial for the large-scale application of PEM water electrolysis technology coupled with renewable energy hydrogen production, but it is also very challenging.

[0003] Ru is several times cheaper than Ir and has a higher theoretical OER activity than Ir, so ruthenium-based OER electrocatalysts are promising alternative materials. However, Ru easily dissolves into the electrolyte solution to form RuO4- during the OER process, resulting in poor stability of the catalyst, and it is currently not possible to achieve industrial application. Therefore, the OER catalytic activity and operational stability of Ru-based catalysts still need to be further improved to meet the requirements of practical applications. Summary of the invention

[0004] In order to improve the activity and stability of ruthenium oxide catalysts in the OER process, it is necessary to improve the performance of each active site and increase the number of active sites. Due to the incomplete crystal structure or the presence of more defects and amorphous regions, low-crystallinity catalysts have more active sites and defect sites on their surfaces, which can promote the adsorption and desorption of reaction intermediates, thereby improving the activity of the catalyst. At the same time, the introduction of transition metals into ruthenium oxide can further adjust the intrinsic activity and stability of ruthenium oxide, and can also reduce the use of precious metal Ru, saving production costs. In order to solve the above problems and achieve the above goals, the present application provides a low-crystallinity rutile phase ruthenium manganese oxide catalyst and its preparation method and application, which has the characteristics of high catalytic activity and stable catalytic effect.

[0005] This application adopts the following technical solutions:

[0006] According to one aspect of the present application, a method for preparing a low-crystallinity rutile phase ruthenium manganese oxide catalyst is provided, comprising the following steps:

[0007] S1, adding Mn3O4 powder to a Ru precursor solution containing Ru ions, reacting to obtain a mixed ruthenium manganese oxide precursor suspension;

[0008] S2, centrifuging, washing, and drying the mixed ruthenium manganese oxide precursor suspension to obtain a mixed ruthenium manganese oxide precursor powder;

[0009] S3, calcining the mixed ruthenium manganese oxide precursor powder to obtain the low crystallinity rutile phase ruthenium manganese oxide catalyst.

[0010] Optionally, in step S1, the Ru precursor solution contains metal Ru salt.

[0011] Optionally, the metal Ru salt is selected from at least one of ruthenium chloride, ruthenium acetylacetonate, ruthenium acetate, carbonyl ruthenium, and nitrosyl ruthenium nitrate.

[0012] Optionally, in step S1, the molar ratio of Ru ions to Mn3O4 is greater than or equal to 2.

[0013] In the reaction described in step S1, the molar ratio of Ru ions to Mn3O4 is greater than or equal to 2, so that the ruthenium ions can simultaneously etch (or ion exchange) the trimanganese tetraoxide. A ratio lower than this ratio will result in incomplete or no etching, resulting in the product having only a simple mixed structure of Mn3O4 / RuO2. In the present application, a ratio greater than or equal to 2 can completely destroy the structure of the trimanganese tetraoxide, and then the precursor powder is heated to form a low-crystallinity rutile phase ruthenium manganese oxide.

[0014] Optionally, in step S1, the molar ratio of Ru ions to Mn3O4 is 2 to 4:1.

[0015] Optionally, in step S3, the molar ratio of Ru element to Mn element in the low crystallinity rutile phase ruthenium manganese oxide is 1:0.1-0.5.

[0016] Optionally, in step S1, the reaction conditions include: carrying out the reaction under stirring or ultrasonic treatment conditions, and the reaction time is 2 to 48 hours.

[0017] Optionally, in step S1, the method for preparing Mn3O4 powder includes: forming a Mn3O4 suspension under heating and stirring conditions from a mixed solution containing a manganese source and an alcohol, and then centrifuging, washing, and drying to obtain Mn3O4 powder.

[0018] Optionally, in step S3, the calcination conditions include: a calcination temperature of 150 to 500° C. and a calcination time of 1 to 20 hours.

[0019] According to another aspect of the present application, a low-crystallinity rutile phase ruthenium manganese oxide catalyst prepared by the above-mentioned preparation method is provided, wherein the low-crystallinity rutile phase ruthenium manganese oxide catalyst has a particle structure formed by aggregation of nanoparticles.

[0020] The molar ratio of Ru element to Mn element in the low-crystallinity rutile phase ruthenium manganese oxide is 1:0.1-0.5.

[0021] According to another aspect of the present application, there is also provided a low crystallinity rutile phase ruthenium manganese oxide catalyst prepared by the above preparation method or the use of the above low crystallinity rutile phase ruthenium manganese oxide catalyst as an anode in a water electrolysis system in the field of water electrolysis and hydrogen production.

[0022] The beneficial effects of this application include:

[0023] The preparation method used in the preparation of the catalyst in the present application is first to prepare by simple preparation or directly use commercially available Mn3O4 as a precursor powder, and then prepare a mixed ruthenium manganese oxide precursor by a simple and easy-to-scale method, and then obtain a low-crystallinity rutile phase ruthenium manganese oxide catalyst by calcination in air. The process is simple and controllable to operate, has low requirements for production equipment, and the raw materials are easy to obtain, which is conducive to industrial scale-up production. The low-crystallinity rutile phase ruthenium manganese oxide catalyst prepared in the present application can not only increase the surface active site density through the low crystallinity structure, but also adjust the intrinsic activity and stability of ruthenium oxide by introducing the transition metal Mn into ruthenium oxide to affect the electronic structure of the catalyst, thereby improving the activity and stability of the catalyst in the OER process, but also can reduce the use of precious metal ruthenium and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the X-ray diffraction pattern (XRD) of the low crystallinity rutile phase ruthenium manganese oxide catalyst prepared in Example 1 and Example 2 of the present application.

[0025] Figure 2 are SEM images, wherein a and c are SEM images of the Mn3O4 powder used in Examples 1 and 2 of the present application, respectively, and b and d are SEM images of the low crystallinity rutile phase ruthenium manganese oxide catalyst obtained in Examples 1 and 2 of the present application, respectively.

[0026] Figure 3 TEM images, wherein a and c are TEM images of the Mn3O4 powder used in Examples 1 and 2 of the present application, respectively, and b and d are TEM images of the low crystallinity rutile phase ruthenium manganese oxide catalyst obtained in Examples 1 and 2 of the present application, respectively.

[0027] Figure 4: is a linear voltammetric curve, wherein a and b are the linear voltammetric curves of the low crystallinity rutile phase ruthenium manganese oxide catalyst obtained in Example 1 and Example 2 of the present application and commercial ruthenium oxide as an oxygen evolution anode material in 1 M H2SO4 electrolyte, respectively.

[0028] Figure 5 This is a stability curve of the low-crystallinity rutile phase ruthenium manganese oxide catalyst material obtained in Example 2 of the present application at a current density of 10 mA per square centimeter. DETAILED DESCRIPTION

[0029] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0030] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0031] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0032] According to one embodiment of the present application, a method for preparing a low-crystallinity rutile phase ruthenium manganese oxide catalyst comprises the following steps:

[0033] (1) providing Mn3O4 powder;

[0034] (2) preparing Ru precursor solution;

[0035] (3) mixing the Ru precursor solution with the Mn3O4 powder, stirring or ultrasonically treating them to allow them to react fully to obtain a mixed ruthenium manganese oxide precursor suspension;

[0036] (4) centrifuging, washing, and drying the mixed ruthenium manganese oxide precursor suspension to obtain a mixed ruthenium manganese oxide precursor powder;

[0037] (5) The mixed ruthenium manganese oxide precursor powder is calcined in air, and after cooling to room temperature, the low crystallinity rutile phase ruthenium manganese oxide catalyst is obtained.

[0038] In the present application, the Mn3O4 powder used can be prepared by oneself or commercially available Mn3O4 powder can be used.

[0039] In the present application, the preparation of the Ru precursor solution includes: dissolving a metal Ru salt precursor in ethanol or deionized water, stirring to completely dissolve it, and obtaining a Ru precursor solution. The metal Ru salt precursor is selected from one or more of Ru chloride, acetylacetonate, acetate, carbonyl ruthenium, or nitrosyl ruthenium nitrate, but is not limited thereto.

[0040] In the present application, when the Ru precursor solution is mixed with the Mn3O4 powder, the amount of Ru in the added Ru precursor solution needs to be excessive, and the molar ratio of the added Ru precursor to Mn3O4 is greater than or equal to 2:1, otherwise the reaction is incomplete and the structure of Mn3O4 cannot be completely destroyed to obtain a pure rutile phase ruthenium manganese oxide catalyst.

[0041] In the present application, the obtained low crystallinity ruthenium manganese oxide has a molar ratio of Ru to Mn of 1:0.1 to 0.5, but is not limited thereto.

[0042] In the present application, the Ru precursor solution is mixed with the Mn3O4 powder and then stirred or ultrasonically treated. Preferably, the treatment time is 12-24 hours.

[0043] In the present application, the mixed ruthenium manganese oxide precursor powder is calcined and cooled to room temperature to obtain the low crystallinity rutile phase ruthenium manganese oxide catalyst. Preferably, the mixed ruthenium manganese oxide precursor powder is placed in a quartz boat and calcined on a heating table or a muffle furnace at a temperature of 150-500°C for 1-20 hours. The calcination temperature does not exceed 500°C, otherwise the Mn2O3 phase may be generated, thereby failing to obtain the pure rutile phase ruthenium manganese oxide catalyst.

[0044] Example 1

[0045] The preparation steps of the low crystallinity rutile phase ruthenium manganese oxide catalyst are as follows:

[0046] (1) Mn3O4 powder was prepared as follows: 2.45 g of Mn(Ac)2·4H2O was dissolved in 100 ml of DEG at 80°C to obtain a mixed solution, and then the mixed solution was heated to 160°C in an oil bath and then maintained for 8 h. During continuous stirring, a brown Mn3O4 suspension was formed. After cooling to room temperature, the suspension was centrifuged, washed with deionized water and ethanol, and then dried at 80°C for 12 h to obtain Mn3O4 powder. 100 mg of the prepared Mn3O4 powder was weighed and dispersed in 10 ml of deionized water, and the mixture was evenly dispersed by ultrasonication for 1 h to obtain a Mn3O4 dispersion.

[0047] (2) Separately, 1 mmol of ruthenium chloride hydrate was dissolved in 10 ml of deionized water and stirred to completely dissolve the hydrate, thereby obtaining a ruthenium chloride solution.

[0048] (3) Add the Mn3O4 dispersion obtained in step (1) to the ruthenium chloride solution obtained in step (2), mix and stir for 24 hours to allow sufficient reaction to obtain a mixed ruthenium manganese oxide precursor suspension.

[0049] (4) The mixed ruthenium manganese oxide precursor suspension obtained in step (3) is separated by centrifugation, and then the precipitate is fully washed with deionized water, and finally dried in an oven at 80° C. to obtain a mixed ruthenium manganese oxide precursor powder.

[0050] (5) The powder obtained in step (4) is placed in a quartz boat and calcined on a heating table at 250° C. for 3 h, and then cooled to room temperature to obtain a low-crystallinity rutile phase ruthenium manganese oxide catalyst. The obtained ruthenium manganese oxide catalyst is analyzed by ICP-OES, and the ratio of ruthenium to manganese is about 3:1.

[0051] Example 2

[0052] The preparation steps of the low crystallinity rutile phase ruthenium manganese oxide catalyst are as follows:

[0053] (1) Weigh 100 mg of commercially available Mn3O4 powder (purchased from Maclean Company) for later use.

[0054] (2) Dissolve 1 mmol of ruthenium chloride hydrate in 20 ml of deionized water and stir to completely dissolve it to obtain a ruthenium chloride solution.

[0055] (3) The Mn3O4 powder weighed in step (1) is added to the ruthenium chloride solution obtained in step (2), and the mixture is stirred for 24 hours to allow the mixture to react sufficiently, thereby obtaining a mixed ruthenium manganese oxide precursor suspension.

[0056] (4) The mixed ruthenium manganese oxide precursor suspension obtained in step (3) is separated by centrifugation, and then the precipitate is fully washed with deionized water, and finally dried in an oven at 80° C. to obtain a mixed ruthenium manganese oxide precursor powder.

[0057] (5) The powder obtained in step (4) is placed in a quartz boat and calcined on a heating table at 250° C. for 3 h, and then cooled to room temperature to obtain a low-crystallinity rutile phase ruthenium manganese oxide catalyst. The obtained ruthenium manganese oxide catalyst is analyzed by ICP-OES, and the ratio of ruthenium to manganese is about 3:1.

[0058] Test Example 1

[0059] The low crystallinity rutile phase ruthenium manganese oxide catalysts obtained in Example 1 and Example 2 were analyzed by X-ray diffraction to obtain their XRD spectra. Figure 1 As shown, the ruthenium manganese oxide catalysts obtained in Example 1 and Example 2 are both rutile phase structures, and have no other diffraction peaks. Compared with commercial ruthenium oxide, the XRD of the catalysts obtained in Example 1 and Example 2 shows weak diffraction peaks and wider peak widths, indicating its low crystallinity.

[0060] The Mn3O4 powder of step (1) in Example 1 and Example 2 was analyzed using a scanning electron microscope to obtain its SEM image, as shown in FIG. Figure 2 a and Figure 2 As shown in Figure c, the homemade Mn3O4 particles are smaller and more uniform than the commercially available Mn3O4 particles. The low crystallinity rutile phase ruthenium manganese oxides obtained in Example 1 and Example 2 were analyzed using a scanning electron microscope to obtain their SEM images, as shown in Figure 5. Figure 2 b and Figure 2 As shown in d, the obtained low crystallinity rutile phase ruthenium manganese oxide catalysts are all in the shape of nanoparticles, and their morphology is different from that of the Mn3O4 raw material used.

[0061] The Mn3O4 powder of step (1) in Example 1 and Example 2 was analyzed using a transmission electron microscope to obtain its TEM image, as shown in FIG. Figure 3 a and Figure 3 As shown in Figure c, the homemade Mn3O4 powder is a nanoparticle with a uniform morphology of about 20 nm, while the commercially available Mn3O4 has no specific morphology and uneven particle size distribution. The low crystallinity rutile phase ruthenium manganese oxide obtained in Example 1 and Example 2 was analyzed using a transmission electron microscope to obtain its TEM image, as shown in Figure 2. Figure 3 b and Figure 3 As shown in Figure d, the obtained rutile phase ruthenium manganese oxide catalysts have similar morphologies, both of which are granular structures formed by aggregation of smaller nanoparticles.

[0062] Application Examples

[0063] The electrochemical performance test method used in this application example is as follows: 4 mg of the low-crystallinity rutile phase ruthenium manganese oxide catalyst powder and 2 mg of carbon black are added to 1 mL of a mixed solution (ethanol: water = 3:1), and then 50 μL of a 5% nafion solution is added, and ultrasonically uniformly mixed to form a catalyst ink. 5 μL of the catalyst ink is dropped on a glassy carbon electrode with a diameter of 3 mm, and after natural drying, it is used as the anode for the electrolysis of water and oxygen evolution reaction. The traditional three-electrode system is selected to determine the catalytic oxygen evolution performance of the material, with 1M H2SO4 as the electrolyte, the glassy carbon electrode after the above-mentioned catalyst ink is dropped and dried as the working electrode, the platinum sheet as the counter electrode, and the saturated calomel electrode as the reference electrode. The linear sweep voltammetry method is used to test the oxygen evolution performance of the material, and the scanning speed is 5 mVs -1 . 300 μL of catalyst ink was dropped on a 1 cm 2 The stability of the catalyst was tested on carbon paper as the working electrode, and the material was tested by chronopotentiometry at 10 mA cm -2 The stability test was carried out at a current density of 2.5 %.

[0064] The electrochemical test method was used to test the low crystallinity rutile phase ruthenium manganese oxide catalysts prepared in Example 1 and Example 2 and commercial RuO2. The results are as follows: Figure 4 As shown in Figures 4a and 4b, the linear voltammetry test results show that the low crystallinity rutile phase ruthenium manganese oxide catalysts prepared in Example 1 and Example 2 have similar electrocatalytic water oxidation activities, indicating that the size and morphology of the precursor Mn3O4 powder particles have little effect on the activity of the low crystallinity rutile phase ruthenium manganese catalyst finally formed. Compared with commercial RuO2, the low crystallinity rutile phase ruthenium manganese oxide catalysts prepared in Example 1 and Example 2 both exhibited better oxygen evolution performance.

[0065] like Figure 5 As shown, at a current density of 10 mA cm -2 The stability was tested by chronopotentiometry at a current density of , and the results showed that the low-crystallinity rutile phase ruthenium manganese oxide catalyst obtained in Example 2 showed better stability than commercial RuO2, indicating that the low-crystallinity rutile phase ruthenium manganese oxide catalyst described in this application and the preparation method thereof are applied to the field of electrocatalytic water oxidation, which can not only reduce the use of precious metal Ru and reduce production costs, but also improve the activity and stability of ruthenium oxide, and have good application prospects in the field of hydrogen production by acidic water electrolysis.

[0066] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a low-crystallinity rutile phase ruthenium manganese oxide catalyst, characterized in that: The steps include: S1, adding Mn3O4 powder to a Ru precursor solution containing Ru ions, reacting to obtain a mixed ruthenium manganese oxide precursor suspension; S2, centrifuging, washing, and drying the mixed ruthenium manganese oxide precursor suspension to obtain a mixed ruthenium manganese oxide precursor powder; S3, calcining the mixed ruthenium manganese oxide precursor powder to obtain the low crystallinity rutile phase ruthenium manganese oxide catalyst.

2. The preparation method according to claim 1, characterized in that: In step S1, the Ru precursor solution contains metal Ru salt.

3. The preparation method according to claim 2, characterized in that: The metal Ru salt is selected from at least one of ruthenium chloride, ruthenium acetylacetonate, ruthenium acetate, carbonyl ruthenium, and nitrosyl ruthenium nitrate.

4. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of Ru ions to Mn3O4 is greater than or equal to 2.

5. The preparation method according to claim 1, characterized in that: In step S1, the reaction conditions include: carrying out the reaction under stirring or ultrasonic treatment conditions, and the reaction time is 2 to 48 hours.

6. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing Mn3O4 powder includes: heating and stirring a mixed solution containing a manganese source and an alcohol to form a Mn3O4 suspension, and then centrifuging, washing, and drying to obtain Mn3O4 powder.

7. The preparation method according to claim 1, characterized in that: In step S3, the calcination conditions include: a calcination temperature of 150 to 500° C. and a calcination time of 1 to 20 hours.

8. The low crystallinity rutile phase ruthenium manganese oxide catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The low-crystallinity rutile phase ruthenium manganese oxide catalyst has a particle structure formed by aggregation of nanoparticles.

9. Use of the low-crystallinity rutile phase ruthenium manganese oxide catalyst prepared by the preparation method according to any one of claims 1 to 7 or the low-crystallinity rutile phase ruthenium manganese oxide catalyst according to claim 8 as an anode in a water electrolysis system in the field of hydrogen production by water electrolysis.

Citation Information

Cited By

  • Low-ruthenium rutile solid solution oxide, preparation method and application of low-ruthenium rutile solid solution oxide in field of electro-catalysis

    CN122406298A